2013
DOI: 10.1063/1.4816117
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure, phonon spectra and electron–phonon interaction in ScB2

Abstract: The electronic structure, Fermi surface, angle dependence of the cyclotron masses and extremal cross sections of the Fermi surface, phonon spectra, electron-phonon Eliashberg and transport spectral functions, temperature dependence of electrical resistivity of the ScB 2 diboride were investigated from first principles using the fully relativistic and full potential linear muffin-tin orbital methods. The calculations of the dynamic matrix were carried out within the framework of the linear response theory. A go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 52 publications
(109 reference statements)
1
3
0
Order By: Relevance
“…ScB 2 shows features in the PD that suggest superconductivity occurs at low temperature (Figure 6b) and experiment shows that the T c for ScB 2 is 1.5 K (as reported by Sichkar and Antonov [56]). However, as shown in Figure 6a, the inverted parabolas around Γ in the EBS are degenerate but ~1 eV below the Fermi level.…”
Section: Diboride Fine Tuningsupporting
confidence: 76%
“…ScB 2 shows features in the PD that suggest superconductivity occurs at low temperature (Figure 6b) and experiment shows that the T c for ScB 2 is 1.5 K (as reported by Sichkar and Antonov [56]). However, as shown in Figure 6a, the inverted parabolas around Γ in the EBS are degenerate but ~1 eV below the Fermi level.…”
Section: Diboride Fine Tuningsupporting
confidence: 76%
“…A notable advantage of these materials is the large linear energy range (> 2 eV), which should facilitate the further experimental study. Furthermore, it has been demonstrated that this family of materials can exhibit a wide range of fascinating properties, such as superconductivity (MgB 2 , TaB 2 , and ZrB 2 ) [38][39][40][41] , super-hardness (OsB 2 , IrB 2 , and ReB 2 ) [42][43][44] , and also excellent thermoelectricity (MgB 2 , and AlB 2 ) 45,46 . Thus our work reveals a promising platform for studying the interplay between these exotic properties and the topological band-crossings.…”
Section: Introductionmentioning
confidence: 99%
“…Kayhan reported a low T c of ∼2 K in WB and MoB compounds. The B6 structure is from the MgB 2 family, frequently studied. ,− …”
Section: Resultsmentioning
confidence: 99%